Integrating an algal β-carotene hydroxylase gene into a designed carotenoid-biosynthesis pathway increases carotenoid production in yeast. (May 2015) - Chang, Jui-Jen; Thia, Caroline; Lin, Hao-Yeh; Liu, Hsien-Lin; Ho, Feng-Ju; Wu, Jiunn-Tzong; Shih, Ming-Che; Li, Wen-Hsiung; Huang, Chieh-Chen
Highlights: Carotenoid biosynthesis genes from green algae. A designed carotenoid biosynthesis pathway in yeast. Bioengineering approaches to reducing manufacturing cost. Abstract: The algal β-carotene hydroxylase gene Crchyb from Chlamydomonas reinhardtii, Czchyb from Chlorella zofingiensis, or Hpchyb from Haematococcus pluvialis and six other carotenoid-synthesis pathway genes were co-integrated into the genome of a yeast host. Each of these three algal genes showed a higher efficiency to convert β-carotene to downstream carotenoids than the fungal genes from Phaffia rhodozyma . Furthermore, the strain with Hpchyb displayed a higher carotenoid productivity than the strains integrated with Crchyb or Czchyb, indicating that Hpchyb is more efficient than Crchyb and Czchyb . These results suggest that β-carotene hydroxylase plays a crucial role in the biosynthesis of carotenoids.